INVENTARISASI TUMBUHAN PARASIT DI TAMAN WISATA ALAM DANAU SICIKEH-CIKEH DESA LAE HOLE KECAMATAN PARBULUAN KABUPATEN DAIRI SUMATERA UTARA - Melfa Aisyah Hutasuhut; Husnarika Febriani; Nur Azizah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2020)
Parasitic plants were usually considered harmful in the forest ecosystem, the changes of parasities is a counterweight to the ecosystem which is expected to tbe able to give benefits to the community. This study was aimed to determine the types of characteristic of parasitic plants in the natural tourist park of Lake Sicikeh-cikeh which was conducted in Oktober-December 2019 by using exploration method or roaming method and by utilizing qualitative descriptive as data collection techniques. The research result showed that were 7 species of parasitic plants were included become 5 families. those were 2 species of Balanophoraceae family, named (Balanophora papuana Schltr. and Rhopalocnemis palloides Jungh.), 2 species of Loranthaceae family, named (Macrosolen avenis Danser and Scurrula sp). 1 species of Santalaceae family, named (Dendromyza reinwardtiana (Blume ex Korth.) Danser), 1 species of Rafflesia family, named (Rafflesia meijeri Wiriad. & Sari), and 1 species of Orchidaceae family, named (Gastrodia sp.). Based on the characteristics of the hosts, Loranthaceae and Santalaceae family were parasite on tree, Balanophoraceae and Rafflesiaceae were parasite on roots and Orchidaceae family with Gastrodia sp. Species were parasite on fungus.